Comprehension of object relatives in Spanish: the role of frequency and transparency in acquisition and adult grammar - Llompart, Miquel; Fernández Santos, Sara; Dabrowska, Ewa (Cognitive Linguistics, 2024)
This study investigates the relative roles of frequency and transparency in native speakers’ comprehension of Spanish object relative sentences by comparing performance with two variants of the construction that differ in these properties. Experiment 1 suggests that seven- to eight-year-old children’s processing of object relative sentences is consistently facilitated by variant frequency and likely relies on separate representations for each variant as two different, although related constructions. Experiment 2 turns to adult comprehension of the two variants, showing similar accuracy and reaction time patterns for both variants for this population. This second outcome could be interpreted as a decrease in frequency effects over time, in line with the power law of practice, as an experience-based increase in the ability to make use of redundant markers, or both.<br
CRIS-Team Scopus Importer:2024-11-01
Keywords: relative clauses; Spanish; first language acquisition; object relatives; Construction Grammar

Redundancy can hinder adult L2 grammar learning: evidence from case markers of varying salience levels - Kenanidis, Panagiotis; Llompart, Miquel; Fernández Santos, Sara; Dabrowska, Ewa (Frontiers in Psychology, 2024)
Grammatical redundancy is a widespread feature across languages. Although redundant cues can be seen to increase the complexity and processing burden of structures, it has been suggested that they can assist language acquisition. Here, we explored if this learning benefit can be observed from the very initial stages of second language (L2) acquisition and whether the effect of redundancy is modulated by the perceptual salience of the redundant linguistic cues. Across two experiments, three groups of adult native speakers of English were incidentally exposed to three different artificial languages; one that had a fixed word order, Verb-Object-Subject, and two in which thematic role assignment was additionally determined by a low-salient (Experiment 1) or a high-salient (Experiment 2) redundant case marker. While all groups managed to learn the novel language, our results pointed towards a hindering role of redundancy, with participants in the non-redundant condition achieving greater learning outcomes compared to those in both redundant conditions. Results also revealed that this impeding effect of redundancy on L2 learners can be attenuated by the salience of the redundant cue (Experiment 2). In conjunction with earlier findings, the present results suggest that the effect of redundancy on L2 acquisition can be differentially manifested depending on the stage of L2 development, learners’ first language biases and age.
CRIS-Team Scopus Importer:2024-06-14
Keywords: artificial language learning; grammar; redundancy; salience; second language acquisition